Цикадки рода Macropsidius Rib. (Homoptera, Auchenorrhyncha, Cicadellidae) на Кавказе - Логвиненко, В.Н. (Вестник зоологии, 1981)
New species of the genus Macropsidius are described: M. ilandagicus sp. n. (the Nakhichevan ASSR) froma group of species with an unflattened cylindrical penis trunk; M. chazarianus sp. n. (Daghestan with a dorsoventrally flattened penis trunk and deve. loped laterallaminar widenings in the basal part of the trunk; M. tricostats sp. n. (Nakhichevan ASSR) distinguished for developed both dorsal and lateral crests on the penis trunk A key is given for 9 species of the genus Macropsidius inhabiting the Caucasus.